Posted by **Sara** on Monday, January 9, 2012 at 11:07am.

log5 (x+3)= 1- log5 (X-1) where do I start?

- precalculus -
**Steve**, Monday, January 9, 2012 at 11:32am
start by collecting logs:

log5 (x+3) + log5(x-1) = 1

now recall that sum of logs is log of product

log5 [(x+3)(x-1)] = 1

raise 5 to the power of both sides:

(x+3)(x-1) = 5

x^2 + 2x - 3 = 5

x^2 + 2x - 8 = 0

(x+4)(x-2) = 0

x = 2 or -4

Since logs of negative numbers do not exist, we have to throw out x = -4 since it does not fit the original equation.

x=2 is our only solution.

check:

log5 (2+3) = 1 - log5 (2-1)

log5 5 = 1 - log5 1

1 = 1 - 0

## Answer this Question

## Related Questions

- precalculus - solve the logarithmic equation . express solution in exact form ...
- Algebra 2 - Express as a logarithm of a single number or expression: 1. 5log4^p+...
- Algebra II - Log6(6^9)=??? Answer: 9 Ine^-3x=??? Answer: -3x Use log5(2) = 0....
- mathematics - Given that log5 3=0.683 and log5 7=1.209.without using calculator...
- Logs-Algebra - How do you graph the following logs? f(x)=log5 (x-2) f(x)=log5 x-...
- Algebra II - Use log5(2)=0.4307 and log5(3)=0.6826 to approximate the value of ...
- logarithms - 5^x=5^-6 Take the log base 5 of each side: log5 5^x=log5 5^-6 x= -6...
- Algebra - How come log5 25^4 reduces to 4 log5 25 then 4 times 2 then finally ...
- college algebra - solve the logarithmic equation. Please show all work. log5x+...
- Maths - Solve for x: log5(x-2)+ log5 (x-4) = log6(x-1)